Functional role of fouling community on an artificial reef at the northern coast of Rio de Janeiro State, Brazil (Brazilian Journal of Oceanography, 2006)
The northern coast of Rio de Janeiro State lacks natural consolidate substrates, making it a proper environment to the development of researches using artificial structures. After studies about the type of substrate, concrete seems to be the most appropriate for studying fouling community development. This research was carried out to investigate the functional role of biofouling in the development of the ichthyic community in the north of Rio de Janeiro State. Percentage data of the epibenthic organisms' coverage and samples of the fish community with gillnet and visual census showed that biofouling in artificial reefs might have more than one functional role, acting as a facilitator in the recruitment of fish species and as a link in the trophic marine chain. Through the increase of localized structural complexity provided by the reef itself and by the fouling organisms which act as "engineering species", additional protection options are offered to the ichthyic community, especially recruits. Also, the epibiont biomass represents an important link in the food web, acting either as a direct source or in the transference of energy to higher trophic levels. Through the relationship between the ichthyic and fouling communities we concluded that the functional role of the latter in artificial reef habitats could be characterized mainly as shelter and feeding grounds for few fish species.